Demonstrating the Value of an ACL Registry. Issue 7 (30th July 2018) - Maletis, Gregory B.; Funahashi, Tadashi Ted; Love, Rebecca; Wyatt, Ronald; Prentice, Heather A.; Burfeind, William; Paxton, Liz
Objectives: One purpose of a registry is to identify procedures or devices that have either good or poor outcomes and improve treatment outcomes through feedback to surgeons. In 2010 we initially reported the influence of graft choice on the risk of early revision after ACL Reconstruction (ACLR). In 2012 we reported a three times higher risk of revision if allograft was used rather than bone-patellar tendon-bone (BPTB) autograft. In subsequent studies of allografts, we have identified poorer results with BPTB allografts compared to soft tissue allografts and with soft tissue allografts irradiated with > 1.8 Mrads or processed with chemical methods. Patients< 21 years of age were also identified to be at particularly high-risk for revision if allograft tissue was employed. These registry findings were disseminated to surgeons within and outside our integrated healthcare system. The purpose of this study was to evaluate the impact of registry feedback on surgeon graft type selection. Methods: Feedback to surgeons on graft performance was presented through a variety of mechanisms including (1) peer-reviewed publications, (2) internal and external meetings and conferences (3) newsletters of study findings, (4) Risk calculators and (5) confidential individualized reports of surgeon's outcomes. In addition, surgeon champions set a quality improvement goal to reduce allograft usage overall and specifically to decrease the use of high risk grafts and usage in high-risk patient groups. Allograft usage was monitored on a quarterly basis to determine if the target was achieved. Annual graft utilization from 2008-2015 is reported here as proportions, for the overall cohort and for high-risk subgroups. Results: Our integrated healthcare system's ACLR registry currently includes over 35, 000 patients. Beginning in 2008, the annual proportion of ACLR cases using an allograft increased with a peak of 45% in 2010. Allograft use has decreased in the ensuing years and was 33% in 2015, a decrease of 27%. High-risk graft usage decreased from 8% in 2011 to 5% in 2015 which is a 38% decrease. Allograft use in patients< 21 years of age decreased 68% from a high of 28% in 2009 to 9% in 2015. (see Figure) Conclusion: Translating registry findings into evidence-based clinical practice is the goal of a registry. In this study, we found that information derived from an ACL Registry and disseminated to the participants can directly influence the use of specific procedures or implants that are associated with poor outcomes. Registries can provide useful information that may ultimately be used to improve patient care.